2018
DOI: 10.1051/0004-6361/201833330
|View full text |Cite
|
Sign up to set email alerts
|

HD 38858: a solar-type star with an activity cycle of ∼10.8 yr

Abstract: Context. The detection of chromospheric activity cycles in solar-analogue and twin stars can be used to place the solar cycle in a wider context. However, relatively few of these stars with activity cycles have been detected. It is well known that the cores of the Ca II H&K lines are modulated by stellar activity. The behaviour of the Balmer and other optical lines with stellar activity is not yet completely understood. Aims. We search for variations in the Ca II H&K, Balmer, and Fe II lines modulated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Furthermore, Flores et al (2016) showed observational evidence of modulations (∼2 mÅ) of the equivalent widths (hereafter EW) of Fe II lines with the chromospheric cycle of the solar twin HIP 45184 (with ∼5.1 yr activity cycle and S = 0.173). However, Flores et al (2018) were not able to find the similar modulations in HD 38858 (∼10.8 yr activity cycle). Precise spectroscopic measurements in the Sun over more than three decades (Livingston et al 2007), show small but measurable variations in some spectral lines (including some strong Fe I lines), but their dependence on the solar activity cycle is not well-established yet.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, Flores et al (2016) showed observational evidence of modulations (∼2 mÅ) of the equivalent widths (hereafter EW) of Fe II lines with the chromospheric cycle of the solar twin HIP 45184 (with ∼5.1 yr activity cycle and S = 0.173). However, Flores et al (2018) were not able to find the similar modulations in HD 38858 (∼10.8 yr activity cycle). Precise spectroscopic measurements in the Sun over more than three decades (Livingston et al 2007), show small but measurable variations in some spectral lines (including some strong Fe I lines), but their dependence on the solar activity cycle is not well-established yet.…”
Section: Introductionmentioning
confidence: 78%
“…Recent multi-year long-term surveys of sizeable samples of F-M (Cincunegui et al 2007) and F-G-K stars (Gomes da Silva et al 2014) provide a perplexingly wide variety of cases, from well-correlated to independent and even anticorrelated behavior of the CaII and Hα line fluxes (Cincunegui et al 2007). For example, in two solar analogs, HD 45184 (Flores et al 2016) and HD 38858 (Flores et al 2018), the rising line-core fluxes (line-filling and shallowing in a typical reaction to a rising stellar activity) in the CaII H&K doublet lead to a stronger (deeper) profile of the Balmer Hβ line.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant CLEAN periods are indicated in each panel. Baliunas et al 1995;Metcalfe et al 2010;Gomes da Silva et al 2011;Flores et al 2018b), enables us to reduce the rotational scatter originated by individual active regions. Following Zechmeister & Kürster (2009), we computed the Generalised Lomb-Scargle periodogram (hereafter GLS) and the false-alarm probability (hereafter FAP, see their equation 24) of each significant peak present in the periodograms.…”
Section: Stellar Activity Analysismentioning
confidence: 99%